Freedom and Information Assessing Publicly Available Data Regarding U.S. Transportation Infrastructure Security - Landree, Eric (RAND Corporation, 2006)
Describes a framework to guide assessments of the availability of data regarding U.S. anti- and counterterrorism systems, countermeasures, and defenses for planning attacks on the U.S. air, rail, and sea transportation infrastructure. Overall, the framework is useful for assessing what kind of information would be easy or hard for potential attackers to find.